The Improving Convenience Store Customer Services with a Queuing system in Udon Thani Rajabhat University Sam Phrao Campus - Pluapant, Ariyapong; Pawaree, Narathip (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
In this research improved customers service convenience store in Udonthani Rajabhat University Samprao campus. The objective is to analyze the appropriate channel of payment in stores and improve efficiency in service and customer satisfaction are: 1) The analysis of queuing system for suitability. Find a convenience store Dormitories male and female suggestions to increase the staff at 11.30-13.00 am. It was time to get a customer service possible and Dormitories female recommended to increase one channel service and convenience stores can reduce the average time by 23 percent and 50 percent respectively, suitable for customers satisfaction. 2) The research is study in customer satisfaction by focus on manage of convenience shop averaging 4.67 with the highest satisfaction. The serving staff’s customer satisfaction averages 4.37, which is high, and the convenience shop has a great, suitable average of 4.46.